2014
DOI: 10.1002/apj.1822
|View full text |Cite
|
Sign up to set email alerts
|

Economic pre‐feasibility study for physical conversion of polyethylene terephthalate wastes to activated carbon

Abstract: Beneficial use of waste polymers is an important issue for environmental protection researchers. In this study, a brief summary has been presented for recycling methods of polyethylene terephthalate (PET) wastes. An economic pre‐feasibility study has been performed for the production of activated carbon from PET wastes. The proposed plant was used the physical activation process for the production of 10 000 t of activated carbon per year. The mass and energy balances and equipment designs of the process were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The produced carbon materials can be an adsorbent candidate for water decontamination with cheap cost, large scale, and chemical stability (such as eliminating radioactive metals, methylene blue dyes, etc.) [32][33][34]. Moreover, functional carbon materials with unique micro-or nano-structures can also be obtained by using different precursors from waste PET, including hierarchical porous carbon for symmetric supercapacitors [35], carbon nanofibers for multifunctional surfaces [31], carbon nanotubes [36], magnetic carbon nanomaterials [37], graphene [38], etc., as shown in Fig.…”
Section: The Carbon Resources In Waste Petmentioning
confidence: 99%
“…The produced carbon materials can be an adsorbent candidate for water decontamination with cheap cost, large scale, and chemical stability (such as eliminating radioactive metals, methylene blue dyes, etc.) [32][33][34]. Moreover, functional carbon materials with unique micro-or nano-structures can also be obtained by using different precursors from waste PET, including hierarchical porous carbon for symmetric supercapacitors [35], carbon nanofibers for multifunctional surfaces [31], carbon nanotubes [36], magnetic carbon nanomaterials [37], graphene [38], etc., as shown in Fig.…”
Section: The Carbon Resources In Waste Petmentioning
confidence: 99%
“…The PET has more carbon in the molecular chain (above 60%), and its pyrolysis yields a higher amount of carbon as a residue 34 . It is reported that the activated carbon from waste PET finds application as an adsorbent in natural gas storage, 35 CO 2 capture, 36,37 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…33 The PET has more carbon in the molecular chain (above 60%), and its pyrolysis yields a higher amount of carbon as a residue. 34 It is reported that the activated carbon from waste PET finds application as an adsorbent in natural gas storage, 35 CO 2 capture, 36,37 and so forth. The carbon procured after pyrolysis has various characteristics, such as a large surface area, less functional groups and low concentration of impurities than the carbon collected from biomass pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (ethylene terephthalate) can be produced from two initial reactions: by esterification, in which terephthalic acid (TPA) reacts with ethylene glycol (EG), and also by the transesterification reaction, by reacting dimethyl terephthalate (DTM) with ethylene glycol (EG) (Torrik, Nejati, & Soleimani, 2014).…”
Section: Introductionmentioning
confidence: 99%